ELABORATION AND EVALUATION OF THE INTERNAL CONSISTENCY OF THE QUESTIONNAIRE OF PERCEPTIONS ABOUT KNOWLEDGE TOWARDS PROFESSIONAL ETHICS IN PHYSIOTHERAPY STUDENTS - Marques-Sule , E; Aguilar-Rodríguez , M; Dueñas-Moscardó , L; Serra-Añó , P (Cuestiones de Fisioterapia, 2017)
Background: the creation and evaluation of questionnaires in the university context is needed, in order to be applied in the assessment of new teaching models. This study aims at presenting the creation and the assessment of internal consistence of the Questionnaire of Perceptions about Knowledge towards Professional Ethics. Material and method: a questionnaire that analyzed perceptions about knowledge towards professional ethics in Physio-therapy students was created, by means of a study carried out with students in the last year of the university course (n = 100). An analysis of internal consistency (Cronbach´s Alfa) was carried out. Predictive Analytics Software (PASW) 18.0 (SPSS Inc., Chicago, IL, USA) was used for statistical analysis. Results: the questionnaire showed an acceptable internal consistency (Cronbach´s Alfa = 0.760). On the other hand, two items showed an item-total correlation or (iHc) < 0.20, but it was decided not to remove them. Finally, the questionnaire was composed of 19 items. Conclusions: CCEPFIS shows internal consistency to be used as a tool of data collection to analyze perceptions about knowledge towards professional ethics in physiotherapy students.